Pengembangan Aplikasi E-Jurnal Kalbisocio dan Kalbiscientia Kalbis Institute - Rusli, Muhammad; Gatc, Jullend; Alifah Wardhani, Annisa (KALBISCIENTIA Jurnal Sains dan Teknologi, 2019)
The aim of this research is developing e-jornal for journal Kalbisocio that focuses in management and communication science, and Kalbiscientia that focuses in science and technology. They are published by Kalbis Institute. The journal management is run by the publisher manualy, therefore the publication cannot be worth and realize. Enhancing to manage the journals, is should be an e-journal that assists all the editor team, reviewer, and author to do thier activities. The e-jurnal can be accesed and manage online by editor team, reviewers, and authors. Hence editor team can control all article processing and decide what to do with their problem in order that the articles can be published on time. Developing e-journal will use prototyping method that meets the need of Kalbisocio and Kalbiscientia. The research will develop an e-journal which assist all editor team, reviewers, and authors to do their activities in journal management.